2015
DOI: 10.12968/jowc.2015.24.12.572
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and cost-effectiveness of an externally applied electroceutical device in managing venous leg ulcers in clinical practice in the UK

Abstract: Within the study's limitations, use of the EAE device potentially affords the NHS a cost-effective treatment for managing VLUs when compared with patients remaining on their previous care plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…The natural history of VLUs is of a continuous cycle of healing and breakdown over decades: VLUs are typically painful and heal slowly, resulting in an impaired quality of life (QoL), social isolation and reduced work productivity . Treatment of this major health problem results in a considerable cost to the National Health Service (NHS): each ulcer costs up to £1981 per year; estimated total healthcare costs are between £198 million and £400 million per year, with 65% of these costs occurring in the community …”
mentioning
confidence: 99%
“…The natural history of VLUs is of a continuous cycle of healing and breakdown over decades: VLUs are typically painful and heal slowly, resulting in an impaired quality of life (QoL), social isolation and reduced work productivity . Treatment of this major health problem results in a considerable cost to the National Health Service (NHS): each ulcer costs up to £1981 per year; estimated total healthcare costs are between £198 million and £400 million per year, with 65% of these costs occurring in the community …”
mentioning
confidence: 99%
“…In Guest et al (2015b)'s study, when applied to VLUs with a mean age of one year, Accel-Heal enabled full wound closure within 2.5 months; when applied to VLUs with a mean age of 6.1 years, it was linked to a 42% reduction in wound size. All patients experienced improved clinical outcomes including a reduction in pain and exudate levels.…”
Section: Electroceutical Treatmentmentioning
confidence: 99%
“…Several studies have demonstrated the costeffectiveness of using electric stimulation for the management of chronic wounds (Clegg and Guest 2007, Taylor et al 2011, Guest et al 2015b. Guest et al (2015b) demonstrated that using an electroceutical treatment for the management of VLUs was a dominant treatment -that is, it resulted in improved outcomes for less cost.…”
Section: Economic Benefits and Implications For Nursing Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have highlighted a new use of electrical stimulation called "electroceutical therapy" that uses electrical stimulation to influence and modify the functions of the body that allow the treatment of various pathologies Through autogenously production of neurotransmitters [13].…”
Section: Introductionmentioning
confidence: 99%